Biodegradable electrospun poly(L-lactide-co-ε-caprolactone)/polyethylene glycol/bioactive glass composite scaffold for bone tissue engineering - de Souza, Joyce R. [UNESP]; Cardoso, Lais M. [UNESP]; de Toledo, Priscila T. A. [UNESP]; Rahimnejad, Maedeh; Kito, Letícia T.; Thim, Gilmar P.; Campos, Tiago M. B.; Borges, Alexandre L. S. [UNESP]; Bottino, Marco C. (Wiley, 2024)
The field of tissue engineering has witnessed significant advancements in recent years, driven by the pursuit of innovative solutions to address the challenges of bone regeneration. In this study, we developed an electrospun composite scaffold for bone tissue engineering. The composite scaffold is made of a blend of poly(L-lactide-co-ε-caprolactone) (PLCL) and polyethylene glycol (PEG), with the incorporation of calcined and lyophilized silicate-chlorinated bioactive glass (BG) particles. Our investigation involved a comprehensive characterization of the scaffold's physical, chemical, and mechanical properties, alongside an evaluation of its biological efficacy employing alveolar bone-derived mesenchymal stem cells. The incorporation of PEG and BG resulted in elevated swelling ratios, consequently enhancing hydrophilicity. Thermal gravimetric analysis confirmed the efficient incorporation of BG, with the scaffolds demonstrating thermal stability up to 250°C. Mechanical testing revealed enhanced tensile strength and Young's modulus in the presence of BG; however, the elongation at break decreased. Cell viability assays demonstrated improved cytocompatibility, especially in the PLCL/PEG+BG group. Alizarin red staining indicated enhanced osteoinductive potential, and fluorescence analysis confirmed increased cell adhesion in the PLCL/PEG+BG group. Our findings suggest that the PLCL/PEG/BG composite scaffold holds promise as an advanced biomaterial for bone tissue engineering.
Keywords: bioactive glass; biopolymers; bone regeneration; electrospinning; scaffolds; tissue engineering